Avaliação do intemperismo no desempenho viscoelástico de compósitos de fibras de carbono/resina furfurílica - Matioli, Aline Vanessa [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Polymeric structural composites are widely applied in engineering due to the combination of low specific mass and high value of mechanical strength and stiffness, these findings their application in the aeronautical industry. It is important to evaluate the environmental effects such as incident ultraviolet radiation and moisture of aeronautical composites, the climatic factors directly affect the behavior and durability of the composites. Thus, in order to meet the special needs required in the aerospace engineering, such as low porosity, low gas emission and lightness, associated with the necessity to find other natural sources to obtain polymer resins, this work the aimed was to use the furfuryl resin, a bioresin, to obtain a new composite, replacing the traditional phenolic resins, reinforced with carbon fibers and processed in a hydraulic press with controlled cooling, and to evaluate the weathering in the viscoelastic performance of the laminate. For this, the techniques of differential scanning calorimetry and thermogravimetry were used to survey the most suitable curing cycle to be used during the processing of this composite. The characterization of the composite was carried out by optical and scanning electron microscopies analysis, interlaminar shear strength test, dynamic-mechanical analysis (before and after environmental conditioning), ultrasonic analysis, acid digestion test, and vibration. From the obtained results, it can be concluded that all the preparation of the composite occurred with quality, because the synthesis resin was a success, and its physicochemical properties were in agreement with the literature. It was noticed that the occurred satisfactorily from the hot compression molding, as evidenced by the characterizations. However, the samples exposed to environmental conditioning ... (Complete abstract click electronic access below)

Os compósitos poliméricos estruturais são muito aplicados na engenharia, devido à combinação da baixa massa específica e alto valor de resistência mecânica e rigidez, o que aumenta seu potencial de aplicação na indústria aeronáutica. É fundamental a avaliação dos efeitos ambientais tais como radiação ultravioleta incidente do sol e umidade nos compósitos aeronáuticos, pois estes fatores climáticos afetam diretamente o comportamento mecânico e durabilidade dos compósitos. Sendo assim, de forma a atender as necessidades especiais requeridas na área de engenharia aeroespacial, tais como baixa porosidade, baixa emissão de gases e leveza, associado à necessidade de se encontrar outras fontes naturais para a obtenção de resinas poliméricas, este trabalho teve como objetivo utilizar a resina furfurílica, uma bioresina, na obtenção de um novo compósito, em substituição às tradicionais resinas fenólicas, reforçado com fibras de carbono e processado em uma prensa hidráulica com resfriamento controlado, e avaliar a influência do intemperismo no desempenho viscoelástico do laminado. Para isso, utilizou-se das técnicas de análises de calorimetria exploratória diferencial e termogravimetria para o levantamento do ciclo de cura mais adequado a ser utilizado durante o processamento deste compósito. A caracterização do compósito foi realizada a partir das análises por microscopias óptica e eletrônica de varredura, resistência ao cisalhamento interlaminar, análise dinâmico-mecânica (estas antes e após os condicionamentos ambientais), análise por ultrassom, digestão ácida, e vibração. A partir dos resultados obtidos pode-se concluir que todas as etapas para a confecção do compósito ocorreram com qualidade, pois a síntese da resina ocorreu com sucesso, e suas características ... (Resumo completo clicar endereço eletrônico abaixo)
Evaluation of weathering in viscoelastic performance of carbon fiber / furfuryl resin composites
Keywords: Compósitos poliméricos; Fibras de carbono; Polímeros; Polymeric composites